Facile synthesis of N-MgSb2O6 trirutile antimonate and its enhanced photocatalytic performance. Issue 19 (30th December 2022) - Nagarajan, Arunkumar; Naraginti, Saraschandra
ABSTRACT: In this study, nanocrystallinetrirutile N-doped MgSb2 O6 was prepared by a facile solution combustion method and its photocatalytic activity was reported for the first time. Products obtained with different oxidant to fuel ratios (O/F) were in crystalline single phasic N-doped MgSb2 O6 confirmed by X-ray diffraction. The prepared powders were well characterised by using scanning electron microscopy, energy dispersive X-ray analysis, transmission electron microscopy, and X-ray photoelectron spectroscopy. Raman spectra showed all the characteristic peaks of trirutile structure with significant shift and broadening in the nanocrystalline product compared to that of microcrystalline product. UV-visible DRS analysis confirmed the decrease in band gap with an increase in O/F which is in the range of 4.05 eV–3.30 eV. Nearly 96% of p -bromophenol degradation ( p -BP, 10 mg/L) was achieved over nanocrystalline N-doped MgSb2 O6 after 60 min of irradiation at a rate of 0.069 min −1 . Furthermore, radical quantification experiments and electron spin resonance (ESR) analysis revealed that OH and O2 − were the main ROS responsible for photodegradation of p -BP. Hence, this study presented the enhanced photocatalytic activity of combustion synthesised nanocrystalline N-doped MgSb2 O6 for the first time and its activity was found to be correlated with N-doping, cation ordering, particle size, and crystallinity.